The digitalization era: philosophical aspects of technological civilization in modern Kazakhstan - Kozhan, A.A.; Yilmaz, S.; Osserbayev, Ye.N.; Shadinova, G.A.; Dosaliyev, T.K. (Karagandy University of the name of acad. E.A. Buketov, 2025)
This article delves into the philosophical implications of digitalization in contemporary Kazakhstan, focusing on its transformative impact on education, societal structures, and the aspirations of youth. As the nation navigates the complexities of technological civilization, the interplay between digitalization and cultural identity becomes increasingly critical. The study examines how digital technologies are reshaping educational paradigms, altering social dynamics, and influencing the behaviors and goals of younger generations, reflecting both the challenges and opportunities presented by this digital shift. The research employs a qualitative methodology, integrating philosophical analysis and thematic exploration. It includes a review of relevant literature, case studies, and an interpretative approach to assess the ethical, social, and cultural dimensions of digitalization. Key examples from Kazakhstan’s educational and social contexts illustrate how digital transformation is affecting the nation. By highlighting the philosophical underpinnings of digitalization, the study emphasizes the necessity for a framework that addresses the moral and cultural implications of technological progress. It argues that digitalization not only facilitates modernization but also fosters inclusivity and progressiveness. Ultimately, this article positions digitalization as a vital force in shaping a civilization that harmonizes technology with Kazakhstan’s traditional values and evolving modern needs.
Keywords: civilization; technology; digitalization; youth; society; education; Kazakhstan